Controlling Graphene Wrinkles through the Phase Transition of a Polymer with a Low Critical Solution Temperature. Issue 23 (17th October 2021) - Kwon, Minho; Yang, Jiyeon; Kim, Hanyoung; Joo, Hyeyoung; Joo, Sang‐Woo; Lee, Young Sil; Lee, Hye Jung; Jeong, Seung Yol; Han, Jong Hun; Paik, Hyun‐jong
Abstract: A novel method for controlling reduced graphene oxide (rGO) wrinkles through a phase transition in a solution using a low critical solution temperature (LCST) polymer dispersant has been developed. The polymer dispersant is designed by control of architecture and composition using reversible addition‐fragmentation chain transfer polymerization. Synthesized poly(2‐(dimethylaminoethyl) methacrylate‐ block ‐styrene) (PD b S) can be successfully functionalized on the rGO surface via noncovalent functionalization. PD b S‐functionalized rGO (PD b S–rGO) exhibits good dispersibility in an aqueous phase at room temperature and forms wrinkles on the PD b S–rGO surface because of phase transition at the LCST of the polymer dispersant. The formation of PD b S–rGO wrinkles is controlled by varying the aggregation number of the polymer dispersant on the PD b S–rGO surface that strongly depends on temperature. This is confirmed by transmission electron microscopy, scanning electron microscopy, and Raman spectroscopy ( I D' / I G ratios are 0.560, 0.579, and 0.684, which correspond to 45, 70, and 95 °C, respectively). In addition, the mechanism of wrinkle control is proved by gold nanoparticles that are grown in polymer dispersant on the PD b S–rGO surface. Abstract : The architecture and composition of polymer are designed for the dispersion and low critical solution temperature (LCST) behavior of graphene. LCST behavior provides phase transition and forms wrinkles of graphene. Wrinkles on the graphene are controlled by varying the aggregation number of the attached polymer on graphene. This mechanism is confirmed by gold nanoparticles, which are grown in the polymer.